Bia Music: The Efforts of Traditional Art Inheritance of Art Education Context - Richard Junior Kapoyos; Muhammad Jazuli; Suharto Suharto; Syakir Syakir (International Conference on Science, Education, and Technology, 2022)
Abstrak. This research aimed to see the Bia Music Phenomenon in Batu Village, North Minahasa Regency in an effort to pass on traditional music in the context of art education. Inheriting traditional music is a cultural problem in the dynamics of human life. The process of inheritance is seen as one of the activities of transfer, transmission, ownership between generations in order to maintain tradition in a family tree that moves continuously and simultaneously. The method in this paper uses a qualitative descriptive method, descriptive method is a method in finding facts about the status of a human group, an object, a condition, a system of thought or an event in the present with the right interpretation (Sedarmayanti., Hidayat, 2002). Qualitative research does not merely describe, but more importantly, finds the meaning contained behind it, as a hidden meaning or intentionally hidden (Ratna, 2010). The purpose of inheritance is generally to maintain cultural values from the past, as well as efforts to maintain the arts. This paper aims to discuss the inheritance system in Bia Music as an effort to preserve the existence of the art. By using the inheritance system theory, this paper examines the types of inheritance in the context of art education and the efforts made in the inheritance process in order to maintain the preservation of the existence of traditional arts.